In-Depth Exploration of Human Gut Microbiota: A Review - Maliha Rashid; Dwaipayaan Sinha; Muhammad Usama; Mariam Badam; Maryam Idrees; Saiqa Noureen; Reem Nadeem; Muhammad Mustajab Khan; Shakira Ghazanfar (Kashmir Journal of Science)
Gut microbiota has a significant role in maintaining the overall health in humans and higher animals. Balanced diet, genetic makeup, and use of antibiotics highly influence the microbial population in the gastrointestinal tract. This review article presents a detailed background on the gut microbiota, including its composition and the various factors influencing its diversity and stability. Strategies for maintaining a healthy gut microbiota are explored, along with an examination of the role of neurotransmitters in regulating gut-brain communication. Research shows that machine learning has a huge potential in elucidating the gut microbiome. Wellbeing and health is directly associated with gut microbiome.